ANALISIS PENGARUH TOTAL ASSET, FUND AGE , EXPENSE RATIO DAN PORTOFOLIO TURNOVER TERHADAP KINERJA REKSA DANA PERIODE 2012 - 2014 - Pambudi, Yusuf Satrio; Mahfud, M. Kholiq (Faculty of Economics and Business Diponegoro University, 2016)
Mutual fund An investment vehicle that is made up of a pool of funds collected from many investors for the purpose of investing in securities such as stocks, bonds, money market instruments and similar assets. Mutual funds are Managed by an professional investmen maganer that can manage the fund in accordance with its investmen objectives.The method used is multiple regression analysis with the classical assumption as statistical requirements. The research variables consisted of total assets, fund age, expense ratio and portfolio turnover. Data used in the study include the NAB monthly data, the effective date of mutual funds, expense ratio and portfolio turnover in the period 2012 - 2014. Forty-five conventional mutual funds with the observation period of 3 years cover 15 equity funds, 15 fixed income funds and 15 mixed fund.The results show The partial test showed that total asset and expense ratio give a positive effect and significant on the performance of conventional mutual fund. Portofolio turnover give anegative effect and not significant on the performance of mutual fund. Fund age give a positif effectbut not significant on the performance of mutual fund.